Research progress on the application of wrist-ankle acupuncture combined with rehabilitation therapy in the prevention and treatment of training injuries - Sun, Yanyan; Xu, Tianxing (Frontiers in Physiology, 2026)
Training injuries remain a significant concern for athletes, often resulting in persistent pain and impaired performance. Integrating wrist-ankle acupuncture (WAA), a minimally invasive Traditional Chinese Medicine (TCM) technique, with evidence-based Western rehabilitation offers a promising multimodal approach to managing and preventing such injuries. This review summarizes current research on the combined use of WAA and rehabilitation strategies, focusing on pain modulation, neuromuscular recovery, and injury prevention. WAA’s neurochemical and circulatory benefits complement rehabilitation’s role in promoting muscle adaptation, joint stability, and tissue repair. Collectively, findings suggest that this integrative approach may enhance pain relief and accelerate recovery, though further controlled trials are needed to confirm long-term efficacy and physiological mechanisms.